Competency Committees in Undergraduate Medical Education: Approaching Tensions Using a Polarity Management Framework. (4th June 2019) - Monrad, Seetha U.; Mangrulkar, Rajesh S.; Woolliscroft, James O.; Daniel, Michelle M.; Hartley, Sarah E.; Gay, Tamara L.; Highet, Alexandra; Vijayakumar, Nithya; Santen, Sally A.
Abstract : Implementing competency-based medical education in undergraduate medical education (UME) poses similar and unique challenges to doing so in graduate medical education (GME). To ensure that all medical students achieve competency, educators must make certain that the structures and processes to assess that competency are systematic and rigorous. In GME, one such key structure is the clinical competency committee. In this Perspective, the authors describe the University of Michigan Medical School's (UMMS's) experience with the development of a UME competency committee, based on the clinical competency committee model from GME, and the first year of implementation of that committee for a single cohort of matriculating medical students in 2016-2017. The UMMS competency committee encountered a number of interdependent but opposing tensions that did not have a correct solution; they were "both/and" problems to be managed rather than "either/or" decisions to be made. These tensions included determining the approach of the committee (problem identification versus developmental); committee membership (curricular experts versus broad-based membership); student cohort make-up (phase-based versus longitudinal); data analyzed (limited assessments versus programmatic assessment); and judgements made (grading versus developmental competency assessment). The authors applied the Polarity Management framework to navigate these tensions, leveraging the strengths of each while minimizing the weaknesses. They describe this framework as a strategy for others to use to develop locally relevant and feasible approaches to competency assessment in UME.